Data Quality of Chemotherapy-Induced Nausea and Vomiting Documentation - Beauchemin, Melissa; Weng, Chunhua; Sung, Lillian; Pichon, Adrienne; Abbott, Maura; Hershman, Dawn L.; Schnall, Rebecca (Applied Clinical Informatics, 2021)
Objective The objective of the study was to characterize the completeness and concordance of the electronic health record (EHR) documentation of cancer symptoms among multidisciplinary health care professionals.Methods We examined the EHRs of children, adolescents, and young adults who received highly emetogenic chemotherapy and characterized the completeness and concordance of chemotherapy-induced nausea and vomiting (CINV) documentation by clinician type and by the International Classification of Diseases 10th Revision (ICD-10) coding choice.Results The EHRs of 127 patients, comprising 870 patient notes, were abstracted and reviewed. A CINV assessment was documented by prescribers in 75% of patients, and by nurses in 58% of patients. Of the 60 encounters where both prescribers and nurses documented, 72% agreed on the presence/absence of CINV.Conclusion Most patients receiving highly emetogenic chemotherapy had a documented assessment of CINV; however, many had incomplete or discordant documentation of CINV from different providers by role, implying the importance of incorporating pragmatic knowledge of EHR documentation patterns among multidisciplinary health professionals for EHR phenotyping and clinical decision support systems directed toward cancer-related symptom management.
Keywords: data quality; electronic health records; clinical informatics; UMLS; cancer symptoms